Low disease activity (DAS28≤3.2) reduces the risk of first cardiovascular event in rheumatoid arthritis: a time-dependent Cox regression analysis in a large cohort study. Issue 10 (12th June 2017) - Arts, Elke EA; Fransen, Jaap; Den Broeder, Alfons A; van Riel, Piet L C M; Popa, Calin D
Abstract : Objective: Systemic inflammation appears to contribute to the excess risk of cardiovascular disease (CVD) in rheumatoid arthritis (RA). The objective of this study was to investigate the effect of different levels of disease activity over time, particularly low disease activity and remission, on CVD risk in patients with RA. Methods: Data from the Nijmegen early RA inception cohort were used. The primary outcome was first CVD events within the first 10 years of follow-up. Cut points of the DAS28 for remission (<2.6) and low (≤3.2), moderate (3.2–5.1) and high (>5.1) disease activity were used. The effect of disease activity on CVD risk was analysed using Cox-proportional hazards regression with DAS28 as a time-dependent covariate and also conventionally with time-averaged DAS28 as the primary dependent variable. Results: Low DAS28 (≤3.2) was significantly associated with a reduced risk of CVD (HR 0.65, 95% CI 0.43 to 0.99) compared with DAS28 >3.2, both when included as a time-dependent covariate and as time-averaged DAS28 ≤3.2 (HR 0.52, 95% CI 0.33 to 0.81). Remission had a modest, non-significant protective effect against CVD (HR 0.67, 95% CI 0.43 to 1.07). Conclusion: Results of this study suggest that low disease activity is sufficient to achieve a protective effect against CVD in RA. Apparently, remission defined as DAS28 <2.6 has no additional protective effect against CVD compared with low disease activity. Our results strengthen the use of tight control strategies in daily clinical practice to achieve low stable disease activity or remission in patients with RA as soon as possible.